Inferring reward prediction errors in patients with schizophrenia: a dynamic reward task for reinforcement learning - Li, Chia-Tzu; Lai, Wen-Sung; Liu, Chih-Min; Hsu, Yung-Fong (Frontiers in Psychology, 2014)
Abnormalities in the dopamine system have long been implicated in explanations of reinforcement learning and psychosis. The updated reward prediction error (RPE)—a discrepancy between the predicted and actual rewards—is thought to be encoded by dopaminergic neurons. Dysregulation of dopamine systems could alter the appraisal of stimuli and eventually lead to schizophrenia. Accordingly, the measurement of RPE provides a potential behavioral index for the evaluation of brain dopamine activity and psychotic symptoms. Here, we assess two features potentially crucial to the RPE process, namely belief formation and belief perseveration, via a probability learning task and reinforcement-learning modeling. Forty-five patients with schizophrenia (26 high-psychosis and 19 low-psychosis, based on their p1 and p3 scores in the positive-symptom subscales of the Positive and Negative Syndrome Scale (PANSS)) and 24 controls were tested in a feedback-based dynamic reward task for their RPE-related decision making. While task scores across the three groups were similar, matching law analysis revealed that the reward sensitivities of both psychosis groups were lower than that of controls. Trial-by-trial data were further fit with a reinforcement learning model using the Bayesian estimation approach. Model fitting results indicated that both psychosis groups tend to update their reward values more rapidly than controls. Moreover, among the three groups, high-psychosis patients had the lowest degree of choice perseveration. Lumping patients’ data together, we also found that patients’ perseveration appears to be negatively correlated (p = .09, trending towards significance) with their PANSS p1+p3 scores. Our method provides an alternative for investigating reward-related learning and decision making in basic and clinical settings.